EVALUATION OF RADIATION DOSE IN DIFFERENT POSITIONS AROUND THE PATIENT TABLE DURING INTERVENTIONAL CARDIOLOGY PROJECTIONS. Issue 2 (30th November 2019) - Lahfi, Y; Ismail, A
Abstract: The aim of the present study was to evaluate the radiation exposure around the patient table as relative to the cardiologist position dose value. The dose rates at eight points presuming staff positions were measured for PA, LAO 30° and RAO 30° radiographic projections, and then normalized to the cardiologist's position dose-rate value. The results show that in PA and RAO 30° projections, the normalized dose rate was higher by 9–22% at the right side of the table at a distance of 50 cm, while it was higher up to 31% at the left side for the same measured points in the LAO 30°. The differences of normalized dose rates for the both table sides were lower and decreased at farther positions. The obtained results correspond to the recommendations of staff radiation protection in Cath-labs with regards to X-ray tube and detector positions.